2000
DOI: 10.1046/j.1464-410x.2000.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette–Guérin instillation treatment for carcinoma in situ of the upper urinary tract

Abstract: Objective To analyse the ef®cacy and safety of bacillus Calmette±Gue Ârin (BCG) perfusion treatment for carcinoma in situ (CIS) of the upper urinary tract. Patients and methods Six patients with cytologically diagnosed CIS of the upper urinary tract were treated by BCG instillation via retrograde catheterization using a 6 F ureteric catheter or an 8 F indwelling JJ ureteric stent between the ureter and bladder. BCG (Tokyo 172 strain, 80 mg in 100 mL normal saline) was instilled weekly for 4 or 8 weeks. The ef®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…Recently, we have tended to select a retrograde ureteric catheterization using the Double-J stent, because this method makes it possible to administer BCG without hospitalization. In addition, consistent with previous studies, 4,[8][9][10][11][12][13][14] the present results suggest that the efficacy of this method may be similar to others, if VUR was S-J + D-J 100 9-38 Okubo et al 12 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Recently, we have tended to select a retrograde ureteric catheterization using the Double-J stent, because this method makes it possible to administer BCG without hospitalization. In addition, consistent with previous studies, 4,[8][9][10][11][12][13][14] the present results suggest that the efficacy of this method may be similar to others, if VUR was S-J + D-J 100 9-38 Okubo et al 12 …”
Section: Discussionsupporting
confidence: 92%
“…One of the primary concerns for intrarenal BCG therapy is choosing when to convert to surgical treatment in cases of recurrence. In eight previously reported studies of intrarenal BCG therapy for CIS of the upper urinary tract, 4,[8][9][10][11][12][13][14] 75 renal units were treated according to the same criteria used in the present study, and 20 of the 75 units (27%) showed no response either recurrence. In 20 of these patients, 7 underwent surgical treatment, whereas radiologically documented invasive tumors developed in 9 of the remaining 13 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the appealing results, BCG intracavitary therapy gained interest and was then used as prophylaxis by some authors in pilot trials [19,20,[33][34][35][36] after anterograde or retrograde endourological treatment of papillary tumors or as therapy for residual disease [2, 32,34,35,[37][38][39][40], particularly carcinoma in situ [37][38][39][40][41].…”
Section: Bacillus Calmette-guérinmentioning
confidence: 99%